Contingent capture during search for alphanumerical characters: A case of feature-based capture or of conceptual category membership?. (July 2019) - Baier, Diane; Ansorge, Ulrich
Abstract: To distinguish if search for alphanumerical characters is based on features or on conceptual category membership, we conducted two experiments where we presented upright and inverted characters as cues in a contingent-capture protocol. Here, only cues matching the top-down search template (e.g., a letter cue when searching for target letters) capture attention and lead to validity effects: shorter search times and fewer errors for validly than invalidly cued targets. Top-down nonmatching cues (e.g., a number cue when searching for target letters) do not capture attention. To tell a feature-based explanation from one based on conceptual category membership, we used both upright (canonical) and inverted characters as cues. These cues share the same features, but inverted cues cannot be conceptually categorized as easily as upright cues. Thus, we expected no difference between upright and inverted cues when search is feature-based, whereas inverted cues would elicit no or at least considerably weaker validity effects if search relies on conceptual category membership. Altogether, the results of both experiments (with overlapping and with separate sets of characters for cues and targets) provide evidence for search based on feature representations, as among other things, significant validity effects were found with upright and inverted characters as cues. However, an influence of category membership was also evident, as validity effects of inverted characters were diminished.